Future of small enterprises and small enterprises in futurethe indian scenario - Raju, U. B. (Univerzita Pardubice, 1998)
The spate of reforms storming the economies of the world is sweeping the small enterprise sector as well in one way or the other. The only way for small enterprises all over the globe to survive, sustain and swim in swirling waters of ever growing competition is to transform themselves into lean, mean, fighting machines standing on their own with networked architecture. Towards this, end, the Abid Hussain committee report an small enterprise reforms is both crucial and timely. Accordingly, small enterprises should seek seismic shifts on several dimensions such as technological and organisational ones while according primacy to the customer. The recommendations can be classified into first order, second order reforms depending upon the scale and scope of the reform impact. The paper addresses the issues, concerns and implications of the three categories of reforms on Indian small enterprises. Further, the significant attributes of small enterprises in future are outlined. Clearly, small enterprises are left with the Hobson's choise of shaping up or shipping out of the battlefield sooner or later.
Keywords: Podnikání; malé firmy; Indie; ekonomické reformy